The age of eclecticism : literature and culture in Britain, 1815-1885 - Bolus-Reichert, Christine, 1969- (Columbus : Ohio State University Press, 2009)
"The burden of the past" invoked by any discussion of eclecticism is a familiar aspect of modernity, particularly in the history of literature. This book aims to place this dynamic in a broader context by examining the rise of a manifold eclecticism in the nineteenth century. It focuses on two understandings of eclecticism in the period--one understood as an unreflective embrace of either conflicting beliefs or divergent historical styles, the other a mode of critical engagement that ultimately could lead to a rethinking of the contrast between creation and criticism and of the very idea of the original.
History's diverse beauties -- The philosophy of the nineteenth century -- Eclecticism and literary modernity -- Alfred Tennyson : the originality of medley -- Charles Kingsley : the Alexandrian age -- Matthew Arnold : the second best life -- Walter Pater and Thomas Hardy : "triumph in mutability."
Includes bibliographical references (pages 278-288) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation; Kingsley, Charles, -- 1819-1875 -- Criticism and interpretation; Arnold, Matthew, -- 1822-1888 -- Criticism and interpretation; Pater, Walter, -- 1839-1894 -- Criticism and interpretation; Hardy, Thomas, -- 1840-1928 -- Criticism and interpretation; Hardy, Thomas, -- 1840-1928 -- Criticism and interpretation; Pater, Walter, -- 1839-1894 -- Criticism and interpretation; Arnold, Matthew, -- 1822-1888 -- Criticism and interpretation; Kingsley, Charles, -- 1819-1875 -- Criticism and interpretation; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Criticism and interpretation; Arnold, Matthew, -- 1822-1888; Hardy, Thomas, -- 1840-1928; Kingsley, Charles, -- 1819-1875; Pater, Walter, -- 1839-1894; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892; Tennyson, Alfred, -- 1809-1892.; Kingsley, Charles, -- 1819-1875.; Arnold, Matthew, -- 1822-1888.; Pater, Walter, -- 1839-1894.; Hardy, Thomas, -- 1840-1928.; Tennyson, Alfred, -- 1809-1892 -- analys och tolkning; Kingsley, Charles, -- 1819-1875 -- analys och tolkning; Arnold, Matthew, -- 1822-1888 -- analys och tolkning; Pater, Walter, -- 1839-1894 -- analys och tolkning; Hardy, Thomas, -- 1840-1928 -- analys och tolkning; English literature -- 19th century -- History and criticism; Eclecticism in literature; Éclectisme dans la littérature.; Littérature anglaise -- 19e siècle -- Histoire et critique; LITERARY CRITICISM -- General; Eclecticism in literature; English literature; Literatur; Eklektizismus; Englisch; 18.05 English literature; Engelsk litteratur -- historia -- 1800-talet.; 1800-1899; Criticism, interpretation, etc